Early and Mid-Term Outcomes of Transcatheter Aortic Valve Implantation versus Surgical Aortic Valve Replacement: Updated Systematic Review and Meta-Analysis - Tsahi T. Lerman; Amos Levi; Yeela Talmor-Barkan; Ran Kornowski (Journal of Cardiovascular Development and Disease, 2023)
(1) Background: The use of transcatheter aortic valve implantation (TAVI) for the treatment of severe symptomatic aortic stenosis is expanding significantly. We aimed to perform a meta-analysis comparing the safety and efficacy of TAVI versus surgical aortic valve replacement (SAVR) during the early and mid-term follow-up period. (2) Methods: We conducted a meta-analysis of randomized controlled trials (RCTs) comparing 1- to 2-year outcomes between TAVI and SAVR. The study protocol was preregistered in PROSPERO and the results were reported according to PRISMA guidelines. (3) Results: The pooled analysis included data from eight RCTs totaling 8780 patients. TAVI was associated with a lower risk of all-cause mortality or disabling stroke (OR 0.87, 95%CI 0.77–0.99), significant bleeding (OR 0.38, 95%CI 0.25–0.59), acute kidney injury (AKI; OR 0.53, 95%CI 0.40–0.69) and atrial fibrillation (OR 0.28, 95%CI 0.19–0.43). SAVR was associated with a lower risk of major vascular complication (MVC; OR 1.99, 95%CI 1.29–3.07) as well as permanent pacemaker implantation (PPI; OR 2.28, 95%CI 1.45–3.57). (3) Conclusions: TAVI compared with SAVR during early and mid-term follow-up was associated with a lower risk of all-cause mortality or disabling stroke, significant bleeding, AKI and atrial fibrillation; however, it was associated with a higher risk of MVC and PPI.